Combined puncture and cutting of elastomer membranes: A fracture energy approach. Issue 25 (2nd March 2017) - Triki, Ennouri; Tri, Phuong Nguyen; Gauvin, Chantal; Vu‐Khanh, Toan
ABSTRACT: Resistance to puncture or cutting by pointed blades is an important property of elastomer membranes and glove materials, making it necessary to define a fundamental criterion for measuring this resistance. However, the intrinsic properties controlling puncture/cutting crack propagation are still unidentified. This study has established a simple criterion describing the relationship between true fracture energy and the puncture/cutting process. Several samples of neoprene and nitrile rubber materials 1.6 mm and 3.2‐mm thick were tested using three pointed blades having tip angles of 22.5°, 35°, and 56°. It was found that both friction energy and true fracture energy contributed to global applied energy. True fracture energy, which is useful for in‐depth study of the puncture/cutting process, was independent of material thickness, blade geometry, and blade lubrication. Furthermore, friction energy was approximately twice as great as true fracture energy. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44945. Abstract :